Positive Attitudes and Language Shift: Dynamics of Tae' Language Usage - Rusdiansyah, Rusdiansyah; Kurniawan, Eri; Syihabuddin, Syihabuddin (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research discusses the shift of the Tae' language through a case study of language attitudes and language usage in the city of Palopo, South Sulawesi. The Tae' language, as the identity of the Luwu people, in this case, the city of Palopo, is rarely used as the daily communication language of the people of Palopo. The use of the language in the family environment, which should be the closest domain to the regional language, has also been replaced. The method used in this research is a descriptive qualitative method. This studyÂ uses the instrumentÂ Cohn et al. (2013) in the form of scoring and social factors that can contribute to attitudes. Data analysis of language attitude employing the concepts of Garvin and Mathiot which encompass characteristics such as language loyalty, language pride, and awareness of linguistic norms. Based on the analysis of the data, the researcher found that the Tae' language as the regional language of the people of Palopo or Luwu has experienced a shift. The people in the city of Palopo have a positive attitude towards the Tae' language, but its usage is still minimal, even within the family domain. The Indonesian language dominates the language usage among the people. The positive language attitude does not align with the positive language usage, and it can even be negative in its usage.